A Review of Infections in People Who Use Nonprescription Drugs. Issue 4 (December 2018) - Lang, Raynell; John Gill, M.
Abstract : Abstract: Addiction heightens an individual's risk for infection through both direct and indirect factors. The direct risk of infection from injecting or inhaling substances is well recognized. Indirect pathways, however, such as immunosuppressive effects of some drugs and the social circumstances of addiction may further increase the risk of infection. Approximately 200 million people (5% of the global adult population) use illegal drugs in any given year, and in Canada, this included nearly 5 million people in 2015. For those managing addiction, a customized approach to reduce the risks for infection followed by screening, early diagnosis, and linkage to treatment programs is essential. For those treating infection in persons with substance use disorder, a holistic approach may be required to achieve treatment goals beyond standard management protocols. Teamwork is usually essential involving; the patient, addictions services, social work, pharmacy, and infectious disease specialists all communicating to optimize outcomes. In this review, we aim to highlight common and clinically important infections that interface with addiction medicine, in order to help prevent, identify, diagnose, and optimally treat such infections.